Epidemiological Aspects of Hepatitis B and C Markers in Blood Donors in Kazakhstan; 2000-2011. - Nurbek Igissinov; Dariyana Kulmirzayeva; Cees Th Smit Sibinga; Asiya Turgambayeva (Tehran University of Medical Sciences, 2014)
Transfusion-transmissible infections such as hepatitis B and hepatitis C are among the greatest threats to blood safety for transfusion recipients and pose a serious public health problem. The aim of this study was to assess the epidemiological aspects of hepatitis B and C in Kazakhstani donor's blood over the period 2000-2011.The data were obtained from the annual reports of the Republican Blood Center. The retrospective study was conducted from 2000 to 2011.Over the study period in the republic a growth of volumes of procured blood from 312.4 to 398.0 units was noted, in total equaled to 4,277.8 units. The proportion of blood wasted increased from 8.3% to 8.7%. In the dynamics the proportion of viral hepatitis among all causes of blood wasted decreased from 29% to 15.5% (HBV) and from 33.5% to 9.9% (HCV). The proportion of HBV and HCV in whole blood decreased considerably, in plasma and red cell concentrate the rates changed slightly. The average annual prevalence of HBV and HCV were 2.1% and 1.8%, respectively.Despite the reduction of viral hepatitis rates among blood donors in Kazakhstan the prevalence still remains high. The HBV prevalence is higher compared to HCV, which needs further investigations in the general population to address the issue.